Красивые, дерзкие, злые: [роман] / Анна и Сергей Литвиновы - Литвинова Анна Витальевна (Эксмо, 2019)
Экземпляры: Ф. 10 (20200629) / Инвентарный номер: 47922 / Цена: 120.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Л 64 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44